1991
DOI: 10.2355/isijinternational.31.201
|View full text |Cite
|
Sign up to set email alerts
|

The electrochemistry of SRB corrosion and related inorganic phenomena.

Abstract: Sulfate-reducing bacteria can cause or influence corrosion in both carbon (or low-alloy)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 0 publications
2
23
0
Order By: Relevance
“…The role of FeS in SRBinduced corrosion was emphasized by several authors (77,78,80), but the exact mechanisms are apparently complex and insufficiently understood (51). Newman et al (1991) found the stimulatory effect of FeS to be small upon closer inspection and stated that the increased cathodic surface area provided by FeS was probably more important than its catalytic properties (81). Indeed, corrosion by FeS has so far been reported only for chemically prepared fine suspensions of the minerals (77)(78)(79)120).…”
Section: The Role Of Fes In Iron Corrosionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of FeS in SRBinduced corrosion was emphasized by several authors (77,78,80), but the exact mechanisms are apparently complex and insufficiently understood (51). Newman et al (1991) found the stimulatory effect of FeS to be small upon closer inspection and stated that the increased cathodic surface area provided by FeS was probably more important than its catalytic properties (81). Indeed, corrosion by FeS has so far been reported only for chemically prepared fine suspensions of the minerals (77)(78)(79)120).…”
Section: The Role Of Fes In Iron Corrosionmentioning
confidence: 99%
“…However, once the metallic surface is covered with inorganic corrosion products such as FeS, cathodic reactions become more important drivers of metal oxidation (81). It has been suggested that such cathodic stimulation results from biogenic dissolved sulfides (29,83,104,111).…”
Section: Emic Versus Cmic-emerging Theories In Srb-induced Corrosionmentioning
confidence: 99%
See 1 more Smart Citation
“…Redox potential (Eh) of all water samples lie within a range from -372mV to +202mV as illustrated graphically in Fig.6. Spectrum of redox potential under which microbial life can be found ranges from -450mV to +850mV, where the negative side of the spectrum favours methanogenic bacteria, and the positive side corresponds to iron bacteria (Newman et al, 1991). Thus, the positive redox potential values obtained for samples collected from Forcados River by Beniboye Flow Station and New Calabar River by Wilbross (Nig) Ltd indicate the presence of iron oxidizing bacteria.…”
Section: Water Analysismentioning
confidence: 99%
“…The presence of higher phosphate concentration in EDS spectra indicates the role of phosphorus compounds in addition to sulfides on corrosion reactions. FeS decreases hydrogen over potential and cause cathodic depolarization [46,47]. This sulfide, in turn, reacts with iron (main constituent of steel) to form iron sulfide.…”
mentioning
confidence: 99%